An Overview of Anxiety Levels Among Prolanis Participants at the Islamic Center Primary Clinic Samarinda - Aminah Aminah; Ratno Adrianto; Rizqa Mahardhika; Dedi Priansyah (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Anxiety is common among individuals with chronic diseases such as diabetes and hypertension due to lifelong treatment demands and risks of complications. WHO (2022) reported that one in seven adults experiences a mental disorder, with anxiety being the most prevalent. In Indonesia, the burden of chronic diseases continues to rise, often accompanied by psychological distress. The Prolanis program aims to improve chronic disease management through education, monitoring, and support, yet most studies focus on clinical outcomes rather than mental health. Assessing anxiety among Prolanis participants is essential to ensure holistic patient care. Objective : To describe anxiety levels among Prolanis participants at the Islamic Center Primary Clinic in Samarinda using the Generalized Anxiety Disorder-7 (GAD-7) instrument and provide baseline information for integrating mental health monitoring into chronic disease management. Research Methods / Implementation Methods : This quantitative descriptive study was conducted in August–September 2025 among 30 active Prolanis participants selected through accidental sampling. Anxiety was measured using the validated Indonesian version of the GAD-7 questionnaire. Scores were categorized into minimal, mild, moderate, and severe anxiety. Data collection used self-administered questionnaires assisted by enumerators when needed, and results were analyzed descriptively using mean, median, standard deviation, and frequency distributions. Results : Participants generally showed low anxiety levels. The mean GAD-7 score was 3.00 (SD 2.89), with most respondents experiencing minimal or no anxiety (73.3%). Mild anxiety occurred in 16.7% of participants and moderate anxiety in 10%, with no severe cases. These findings indicate good psychological well-being among participants, potentially supported by Prolanis activities such as routine health checks, group education, exercise sessions, and community support. Similar trends have been reported in several previous studies, suggesting that continuous social interaction and psychosocial support may help reduce anxiety in chronic disease patients. Conclusion / Lesson Learned: Most Prolanis participants experienced minimal anxiety, suggesting that Prolanis contributes positively to both physical and mental health outcomes. Regular monitoring, supportive group activities, and community engagement appear to help maintain emotional stability. Mental health screening, staff training in basic psychological assessment, and strengthened family and community support are recommended to enhance comprehensive chronic disease management.